Consideration of intellectual property law in the context of European Union practice - А. Polishchuk (Law. Human. Environment)
The development of effective legislation on intellectual property in the context of shaping a digital society is an important issue for ensuring the stable development of innovation and protecting creators’ rights. The aim of the work is to analyse the constitutional and international principles of legislative regulation in the field of intellectual property law in the European Union to improve its legal regulation in Ukraine. The scientific basis was the application of the dialectical method as a way to delve deeper into the issues of intellectual property law, as well as the use of methods such as detailing and synthesis, abstraction, analysis and synthesis, and comparative legal method. The peculiarities of legislation on intellectual property in Ukraine and the European Union have been studied, revealing the lack of unified legal regulation of intellectual property issues. Experience confirms that institutional support is necessary for the field of intellectual property in Ukraine. To determine an effective state policy, it is necessary to develop and implement new terminology in the field of copyright protection. In the past, insufficient international cooperation has led to Ukrainian legislation not meeting modern requirements, especially in actively developing areas that require special terms and designations for the protection of intellectual work results. Based on the results of the conducted research, it has been established that the system of intellectual property protection in Ukraine is developing and requires constant improvement. The existence of violations of intellectual property rights indicates the need for the implementation of a programme to improve this system, as state protection of intellectual property is the main aspect of developing an innovative economy and increasing Ukraine’s competitiveness. In other words, due to significant gaps in legislation, manufacturers of innovative products will not rush to introduce them to the Ukrainian market, and high-tech start-ups are not protected from unfair copying of ideas. Also, based on the research results, gaps have been identified in the regulation of legal regimes for texts, music, and images generated by artificial intelligence. The research results can be useful for legislators working on improving legislation on intellectual property and for the development of strategies for managing intellectual property, which will contribute to increasing competitiveness and innovative development of business